GAMBARAN INTERAKSI SOSIAL PASIEN CA MAMMAE YANG MENJALANI KEMOTERAPI DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Rika Elvia; Yulia Irvani Dewi; Hellena Deli (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2023)
Social interaction is the connection between individu to individu, individu to group, and group to group in the form of competition, collaboration or conflict. Social interaction of Ca mammae patients is an important part that influences the quality of life, the effects of chemotherapy that require support and social relationships that can help them overcome psychological stress. This study aims to determine the social interactions of ca mammae patient undergoing chemotherapy. Design of this study was descriptive. Respondents in this study were 78 patients who used accidental sampling technique in Instalasi Kanker Terpadu of Arifin Achmad Hospital, Riau Province. The measuring instrument used was the RAND Health Battery. The analysis used was univariate analysis. Duration of diagnosis < 24 months  had low social interactions (62%), respondents of  third stage had low social interactions (61,5%), and respondents who had chemotherapy at second period and sixth cycle had high social interaction (100%). The results of this study showed that more patients who undergo chemotherapy will be able to adapt to the side effects of chemotherapy. The social interaction of ca mammae patients undergoing chemotherapy were low. The result of this study can be used as a reference for making intervention that help patient to interact with other people and environment.